2020
DOI: 10.1161/hypertensionaha.120.14930
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Sodium Nitrite on Blood Pressure, Insulin Sensitivity, and Intima-Media Arterial Thickening in Adults With Hypertension and Metabolic Syndrome

Abstract: The nitrate-nitrite-NO pathway regulates NO synthase–independent vasodilation and NO signaling. Ingestion of inorganic nitrite has vasodilatory and blood pressure–lowering effects. Preclinical studies in rodent models suggest there may be a benefit of nitrite in lowering serum triglyceride levels and improving the metabolic syndrome. In a phase 2 study, we evaluated the safety and efficacy of chronic oral nitrite therapy in patients with hypertension and the metabolic syndrome. Twenty adult subjects with stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“… 44 , 54 Nitrite and iron-nitrosyl-Hb likely relate inversely to BP changes, as suggested by independent groups 7 , 49 , 55 , 56 and confirmed with recent translational human studies. 57 , 58 …”
Section: Discussionmentioning
confidence: 99%
“… 44 , 54 Nitrite and iron-nitrosyl-Hb likely relate inversely to BP changes, as suggested by independent groups 7 , 49 , 55 , 56 and confirmed with recent translational human studies. 57 , 58 …”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of cardiometabolic disease, no additional beneficial effects on cardiovascular and metabolic parameters were observed when dietary nitrate supplementation was given in combination with metformin 191 , suggesting similar mechanisms of action. A phase II study that investigated the cardiometabolic effects of nitrite therapy (40 mg, three times daily) for 12 weeks in adults with stage 1–2 hypertension, metabolic syndrome and normal kidney function who were not receiving any medications that affect glucose metabolism showed that nitrite gradually lowered blood pressure during the first 8 weeks of treatment (by approximately −10 mmHg), but blood pressure levels started to return to baseline after 10–12 weeks 192 . Hyperinsulinaemic–euglycaemic clamp studies suggested that nitrite supplementation resulted in a trend towards decreased endogenous glucose production and improved insulin sensitivity.…”
Section: Approaches To Restoring No Bioactivitymentioning
confidence: 99%
“…41 In our study, the nitrate intake was $7.5 mmol/d for 3 months, which was increased to oral sodium nitrite (40 mg 3 times a day) reduced CIMT by 0.04 mm from 0.773 ± 0.02 mm at baseline to 0.730 ± 0.02 at 12 weeks (P = .0054) in 20 patients with hypertension and metabolic syndrome. 42 This study provides valuable mechanistic support for an effect of nitrite on CIMT, albeit accompanied by a significant decrease in semi-recumbent SBP and DBP and a significant $11% increase in resting conduit artery diameter (brachial) from 0.36 ± 0.02 mm to 0.40 ± 0.02 mm after 12 weeks of nitrite therapy (P = .0009); this is similar to the acute vasodilatory effect of systemically-infused nitrite we had previously observed. 43 As commented above, our observed effect of dietary nitrate on CIMT was in the absence of changes in BP or carotid diameter.…”
Section: Discussionmentioning
confidence: 99%